2022
DOI: 10.3389/fphar.2022.1016669
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic-guided clozapine administration based on HLA-DQB1, HLA-B and SLCO1B3-SLCO1B7 variants: an effectiveness and cost-effectiveness analysis

Abstract: The identification of pharmacogenetic factors that increase the susceptibility to clozapine-induced agranulocytosis or granulocytopenia (CIAG) has received increasing interest. The SLCO1B3-SCLO1B7 variant (rs149104283) and single amino acid changes in human leukocyte antigen (HLA) HLA-DQB1 (126Q) and HLA-B (158T) were associated with an increased risk of CIAG. In this study, we evaluated the effectiveness and cost-effectiveness of adding the SLCO1B3-SCLO1B7 to HLA variants as a new pharmacogenomic (PGx) approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Age, median (years): 47 Sex (% female): 37.8% Ethnicity: N/A Medication (%): N/A Diagnosis (%): dementia, 0.53; substance-related disorder 6.38; schizophrenia, 67.02; persistent delusional disorder, 1.06; brief and acute psychotic disorder, 0.53; schizoaffective disorder, 6.92; bipolar disorder, 13.30; major depressive disorder, 0.53; specific personality disorder, 1.06; mixed personality disorder, 0.53; intellectual disability, 1.06 Pharmaceutical costs Hospitalization costs Antipsychotics CYP1A2 , CYP2B6 , CYP2C9 , CYP2C19 , CYP2D6 , CYP3A5 and ABCB1 Walden et al 25 2019 Canada Prospective observational study One arm: pharmacogenetics only Assessment points: baseline, 6 weeks and 12 weeks Total sample ( n = 80) offered pharmacogenetics test. Age, mean (years), 43 Sex (% female): 43.8% Ethnicity/race (% of participants): European Caucasian 68.8%, African 3.8%, Asian 3.8%, others 12.5%, mixed 11.3% Medication (%): antipsychotics, 47.5; antidepressants, 23.8; anxiolytics, 7.5; antipsychotics and antidepressants, 11.3; antipsychotics, antidepressants, and anxiolytics, 6.3; no medication, 3.8 Diagnosis: schizophrenia/schizoaffective, 53.8%; anxiety/depression, 40%, others, 6.3% Physician’s opinions (using PIP-FQ) ADRs (UKU) Antidepressants, anxiolytics and antipsychotics CYP2D6 and CYP2C19 Markov/decision models Ninomiya et al 31 2022 United Kingdom Decision tree with Markov model Third-party payer perspective Two arms: pharmacogenetics versus TAU Time horizon: 10 years The target population was adult men and women with treatment-resistant schizophrenia ICER Clozapine SLCO1B3 – SCLO1B7 , HLA-DQB1 and HLA-B Girardin et al 35 2019 United States Decision tree with semi-Markovian model Third-party payer perspective Three arms: (1) PGx-guided clozapine treatment with ANCM for patients who test positive for one or both alleles, (2) PGx-guided clozapine treatment for patients who test negative or alternative antipsychotics for patients who test positive, (3) TAU. Time horizon: 3 years The target population was adult men and women with treatment-resistant schizophrenia ICER Clozapine HLA-DQB1 and HLA-B Kurylev et al 29 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, median (years): 47 Sex (% female): 37.8% Ethnicity: N/A Medication (%): N/A Diagnosis (%): dementia, 0.53; substance-related disorder 6.38; schizophrenia, 67.02; persistent delusional disorder, 1.06; brief and acute psychotic disorder, 0.53; schizoaffective disorder, 6.92; bipolar disorder, 13.30; major depressive disorder, 0.53; specific personality disorder, 1.06; mixed personality disorder, 0.53; intellectual disability, 1.06 Pharmaceutical costs Hospitalization costs Antipsychotics CYP1A2 , CYP2B6 , CYP2C9 , CYP2C19 , CYP2D6 , CYP3A5 and ABCB1 Walden et al 25 2019 Canada Prospective observational study One arm: pharmacogenetics only Assessment points: baseline, 6 weeks and 12 weeks Total sample ( n = 80) offered pharmacogenetics test. Age, mean (years), 43 Sex (% female): 43.8% Ethnicity/race (% of participants): European Caucasian 68.8%, African 3.8%, Asian 3.8%, others 12.5%, mixed 11.3% Medication (%): antipsychotics, 47.5; antidepressants, 23.8; anxiolytics, 7.5; antipsychotics and antidepressants, 11.3; antipsychotics, antidepressants, and anxiolytics, 6.3; no medication, 3.8 Diagnosis: schizophrenia/schizoaffective, 53.8%; anxiety/depression, 40%, others, 6.3% Physician’s opinions (using PIP-FQ) ADRs (UKU) Antidepressants, anxiolytics and antipsychotics CYP2D6 and CYP2C19 Markov/decision models Ninomiya et al 31 2022 United Kingdom Decision tree with Markov model Third-party payer perspective Two arms: pharmacogenetics versus TAU Time horizon: 10 years The target population was adult men and women with treatment-resistant schizophrenia ICER Clozapine SLCO1B3 – SCLO1B7 , HLA-DQB1 and HLA-B Girardin et al 35 2019 United States Decision tree with semi-Markovian model Third-party payer perspective Three arms: (1) PGx-guided clozapine treatment with ANCM for patients who test positive for one or both alleles, (2) PGx-guided clozapine treatment for patients who test negative or alternative antipsychotics for patients who test positive, (3) TAU. Time horizon: 3 years The target population was adult men and women with treatment-resistant schizophrenia ICER Clozapine HLA-DQB1 and HLA-B Kurylev et al 29 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The ICER is the difference in mean costs of two interventions (that is, a new intervention and the standard intervention) divided by the difference in mean health effects, such as quality-adjusted life years (QALY) 30 . Ninomiya et al 31 compared pharmacogenetics-guided clozapine treatment to TAU and calculated an ICER of £16,215 per QALY, that is, it would cost an extra £16,215 to gain an additional QALY if the patient were prescribed antipsychotics using the pharmacogenetics-guided strategy as opposed to the traditional strategy. Similarly, Rejon-Parrilla et al 32 found that pharmacogenetic testing entailed an additional cost of £19,252 per QALY.…”
Section: Resultsmentioning
confidence: 99%